Conservation and management of animal genetic resources in the context of African livestock production systems: The case for in situ and ex situ conservation - Feugang, J.M.; Osei-Amponsah, R.; Rege, J.E.O.; Fantazi, K.; Tiambo, Christian K.; Shumbusho, F.; Houaga, I.; Harek, D.; Dlamini, N.H.; Gaouar, S.B.S. (Springer, 2025)
Conserving and managing African animal genetic resources requires understanding how these resources evolve (political, environmental, cultural, and social). Factors associated with this context are unfavorable for sound conservation and management in most African countries. This chapter presents the major threats to indigenous animal genetic resources (Sect. 25.2) in Africa; the in situ and ex situ conservation methods practiced (Sects. 25.3 and 25.4), operational guidelines (Sect. 25.5), and the opportunities presented by modern technologies (Sect. 25.6). More research structures and skills in reproductive biotechnology and genetics are needed in the continent to ensure the sustainability of animal resources, in particular those with low numbers or less economic interest. Some African countries with constituted herds for conservation (ex situ in vivo) have also taken the initiative to generate gametes, embryos, tissue, and DNA banks. The multi-stakeholder breeders-researchers-decision-makers approach remains the most robust solution for sound management and preservation of biological units.